Pragmatisme: Menepis Keraguan, Memantapkan Keyakinan - Fera Andriani (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2017)
Pragmatism is a madhhab in Philosophy that aims to solve various problems around us. One of the most important figures in Pragmatism was Charles Sanders Peirce. He has a cutting-edge construction of thought. Starting from the nature of belief and its elements are propositions, habits of mind, and discussion of doubts and beliefs. To gain belief, Peirce devised a series of methods: tenacity, authority, a priori, and method of science (inquiry). It is from that inquiry that leads people to discover the nature of truth (Truth) and clarify the ideas that exist in the belief to find meaning (Meaning)